RELASI KIAI-SANTRI DI PESANTREN FUTUHIYYAH, DEMAK - Suparjo Suparjo (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This writing discusses interpersonal relations between kiai and santri which concludes that ethic-pedagogic communication is a result from closed-distanced relation via habituation process based on unifying reflective-ethics conscience with practical conscience in religious patron- age social relation ethics value based. Both value and the practice of ethic- pedagogic communication tradition, in terms of interpersonal communi- cation between kiai and santri, contain positive and negative effects. The sense of kinship becomes an ideal value which should be preserved and adopted in educational system outside pesantren. The charisma-tization and symbolization towards kiai, create more awareness in studying pro- cess and maximizing self development during a period in pesantren and even beyond. Kiai - santri interpersonal communication restores many nega- tive - unproductive attitudes deliberately and ramifies positive - construc- tive side in everyday life. The more reflective conscience arises in many pesantren communities, significantly cementing the tradition. And if this habitus collectively formed and more and more become a tradition, this could affect to each person who enter the pesantren . This transformation into tradition could possibly occured because of the â€œabration of tradi- tionâ€ process.